Peer-to-peer video-on-demand in future internet - Fouda, Mostafa M.; Fadlullah, Zubair Md.; Pathan, Al-Sakib Khan; Kato, Nei (CRC Press, USA, 2013)
The advance in broadband access technology is improving at the proverbial lightning fast speed. As a consequence, in the near future, we can expect to have 40G/100G bandwidth and Ultra High Definition Television (UHDTV) with a resolution of 4320p in contrast with today's 1080p technologies. In this chapter, we describe the recent trends of multimedia, especially video distribution techniques. Also, we point out the urgent need for some of the current content distribution protocols to be reviewed and revised in order to address and accommodate the latest improvements in content distribution technologies. We highlight that the Peer-to-Peer (P2P) protocol is one of the most popular techniques for downloading data, viewing online channels, and/or watching Video-on-Demand (VoD) movies. The chapter specifically addresses the use of P2P protocol in streaming a large volume of VoD data, which is corresponding to the future trends of video quality. Directions are presented toward how to improve P2P based VoD schemes in an effective fashion.